Single-and Double-layer Microwave Absorbers Of Cobalt Ferrite And Graphite Composite At Gigahertz Frequency - Ismayadi Ismail; Khamirul Amin Matori; Zulkifly Abbas; Muhamad Misbah Muhamad Zulkimi; Dr. Fadzidah Binti Mohd Idris; Mohd Hafiz Mohd Zaid; Nurfaziera Rahim; Intan Helina Hasan; Woon Hai Song (Springer Nature, 2024)
Indexed by ERA